The Role of the Mojahedin Khalq Before and After the Islamic Revolution of Iran - Khandagh, Najleh (Advances in Social Sciences Research Journal, 2021)
The Mojahedin Khalq Organization was formed in 1965 with an organizational and religious approach and was one of the political groups that fought against both the Pahlavi regime and the Islamic Republic. The main purpose of this group was to oppose the government and their armed methods. In 1971, after the execution of the organization’s main leaders, members of the organization came to the conclusion that Islam did not meet the organization’s goals for guerrilla and armed operations, and that Marxism could replace Islamic ideology, which were divided into Marxist and religious branches. The religious groups of the Mojahedin Khalq Organization joined Imam Khomeini in 1975, but the Marxist branch, led by Rajavi, fought against the revolution with the idea of seeking supremacy. The main question of this research is how the Mojahedin Khalq Organization has changed its ideological positions and approach to Marxism. In response to this question, it is hypothesized that the Marxist course of the members of the organization gradually began from September 1941 onwards and finally this organization took on a Marxist form and content. This article examines the principles of thought of the Mojahedin Khalq Organization, the process of ideological deviation of the organization and the reason for the failure of the organization and the strategy and performance of this organization after the revolution. The present research has been done using the method of interviews, library and documents in an analytical-descriptive method.